The symbolic dimensions of whale bone use in Thule winter dwellings - Patton, A.; Savelle, James (Études/Inuit/Studies, 2006)
AbstractThe Thule whale bone house is one of the most impressive features of the arctic landscape. Bowhead whale bone elements within 18 Thule winter houses along the southeastern coast of Somerset Island (Nunavut) were mapped and the patterning of these elements was investigated through the application of a bowhead architectural utility index and through principal components analysis. The results suggest that while whale bone was initially selected for dwelling construction on the basis of architectural value, socio-economic status may be reflected in the positioning of certain bone elements. Informed by historic North Alaskan Inupiat analogies, the positioning of various elements within the entrance tunnel in particular appears to have been related to whale symbolism.